(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2022)
The traditional medicine, Cassia alata, also known as Ketepeng Cina in Indonesia and Gelenggang in Malaysia, has been used to cure a variety of illnesses particularly skin conditions. Additionally, it has been suggested that C. alata may have antifungal, anticancer, anti-inflammatory, and antioxidant properties. Alatinon, alanonal, flavones, flavonols, and flavonoid glycosides, as well as -sitosterol-D-glucoside, are among the isolated metabolite substances from C. alata. Mostly from the leaves, chemicals have been isolated. The secondary metabolites from other plant components such as the seed, flower, and bark, which are also said to have strong antibacterial and antifungal activity, need to be further identified. Due to its biological activity and secondary metabolites, this plant has been demonstrated to have pharmacological activities against selected diseases.